殿堂内外：论《马华文学批评大系》及其意义: Literary Canon in the Making: A Discussion on Malaysian Chinese Literary Criticism - Seah, Cheng Ta (ERUDITE: Journal of Chinese Studies and Education, 2020)
从二十世纪末到二十一世纪初的马华文学评论，可说是马华文学评论的黄金年代。整体上，《马华文学批评大系》集合了当今马华文学评论的重量级论述。可再探究的是，《大系》中的这十一人是否足以带来当代马华文学评论的整体景观。这里也可从两个层面思考：一、就《大系》中文章所涵盖的主题而言，议题是否关键且具经典性、评论是否有具备收入选集的价值？二、收入在大系内的评论学者可否为马华文学场域提供重要的见解与思维，甚至是主导当代马华文学的论述？ Abstract The literary criticisms of Malayan Chinese literature from the end of 20th century to 21st century is known to be the “golden generation”. However, there are still voices on the eleven writers if they are able to portray the overall development of contemporary Malayan Chinese Literature. There are two perspectives that can be discussed. Firstly, are the essays well-represented to be incorporated into the compendium? Secondly, are the writers in the compendium able to provide insightful thoughts, or even lead in the narrations of Malayan Chinese literature? Keywords: Malayan Chinese Literature, Literary Criticism, Literary Canon, Choong Yee Voon, Chen Tah Wei